Effects of the Computer Mediated Communication Interaction on Vocabulary Improvement - Siamak Mirzaei; Ashkan Farrokh Hayati (Universitas Ahmad Dahlan, 2018)
This study examined the effect of CMC interaction on Iranian EFL learners’ vocabulary improvement. The study was carried out on the basis of a comparative design and tried to compare CMC with face to-face interactions in the Iranian EFL learners in order to see whether the learners’ lexical knowledge improved by the CMC interaction. Participants of the study were advanced learners studying in a language institute. The Oxford placement test was used to determine the Iranian EFL learners’ proficiency level and ensure a homogeneous sample. Then, the participants were randomly assigned to one control group (face-to-face interaction) and one experimental group (CMC interaction) in order to compare the effect of CMC on the learners’ vocabulary improvement. The learners took a pre-test to select 12 target lexical items, treatment activity to perform information-gap task, and two immediate and delayed post-tests for assessing the acquisition of new lexical items. Yahoo Messenger was used to provide the chat communication. The research provided evidence that there was a significant relationship between the use of CMC interaction and face-to-face interaction with regard to improvement in the learners’ vocabulary learning. The result indicated that the learners’ vocabulary learning improved more in CMC interaction in comparison to face-to-face interaction. In addition, there was a significant difference in negotiating the meaning of new lexical items through CMC interaction in comparison to face-to-face interaction. Moreover, the results indicated that in terms of signal, the CMC interaction outperformed face-to-face group.